The impact of traditional and holistic flipped classrooms on undergraduate students academic writing and autonomy - Behnam Behforouz; Ali Al Ghaithi (Universitas Syiah Kuala, 2025)
This study investigated the effects of two approaches in flipped classrooms, including the traditional model, in which the learners were exposed to blended learning in-class and online, and the holistic model, in which the learners participation was fully online through the specified platforms, on academic writing skills and autonomy. To this end, 60 Omani undergraduates with intermediate English proficiency levels were randomly selected as the sample of the study. They were divided equally into one control group and two experimental groups. Researchers designed pretests and posttests in multiple-choice format, which were used to collect data on writing skills. All the tests were validated, and their reliabilities were measured. A questionnaire from Zhang and Li (2004) was adapted to measure the degree of autonomy among the students during treatment. This questionnaire was piloted before the main study and demonstrated high reliability. The findings of the one-month study revealed that the two experimental groups performed significantly better than the control group, with the blended learning group outperforming the fully online group. These results were consistent for the autonomy questionnaire, confirming that flipping the classes, either fully or partially, helps learners become more independent. The study findings are significant for students, instructors, and institutions.